PERTUMBUHAN DAN HASIL TANAM CABAI RAWIT (Capsicum frustescens L.) YANG DIBERI BERBAGAI PUPUK ORGANIK DAN JENIS MULSA - Muliati, Fitri; Ete, Andi; Bahrudin, Bahrudin (AGROTEKBIS, 2017)
This research was conducted in the Village Poboya, the city of Palu, Central Sulawesi. From December 2014 - April 2015, with the aim to determine the growth and yield of cayenne pepper by organic various fertilizers and type of mulch. This study uses (RAK) factorial design with two factors. The first factor is the organic fertilizer (P) consisting of three (3) types: P0 = Without Organic Fertilizer, P1 = Manure Ram, P2 = Bokasi rest of the plant. The second factor is the type of mulch (M) consisting of three (3) types: M0 = Without mulch, M1 = Rice Straw Mulch, Mulch M2 = Coconut Fiber. There are 9 combined treatment, treatment was repeated 3 times. Each treatment combination was represented by two (2) polybag or two plants so that there are 54 units of the plant (polybag). The results showed no interaction between the various types of organic fertilizers and mulch. Organic fertilizer goat fold give the best results of growth and crop yield compared with Bokashi cayenne and without fertilizer. Similarly, rice straw mulch is better than coconut fiber.Key Words: Cayenne pepper, manure goat, rice straw mulch.